Determinants of high-growth university spin-offs in Spain. Issue 4 (16th October 2019) - Fernández-López, Sara; Rodeiro-Pazos, David; García González, Fernando; Rodríguez-Gulías, María Jesús
Abstract : Purpose: This study aims to determine that the factors that lead to university spin-offs (USOs) high-growth firms (HGFs). In recent years, HGFs have been a topic of growing interest in the field of economic research because of these companies' capacity for job creation and the dynamism they bring to the growth of the economy. In parallel, companies that are born of knowledge or technology developed at universities, known as university spin-offs, have also received attention from the literature in entrepreneurship. Design/methodology/approach: In this study, to analyse the extent to which USOs have become HGFs, a sample of 237 Spanish companies with university origins for a period of study from 2007 to 2014 were used. To contrast the present study's hypotheses, eight different models were estimated using probit models. Findings: The results show that factors such as number of employees, internationalization, profitability and indebtedness positively affect the probability that a USO will become an HGF. However, for age, industry, innovation, the presence of venture capital and productivity, no statistically significant relationship could be found. Originality/value: This study contributes to the literature in HGFs and university entrepreneurship in different ways. First, to the best of the authors' knowledge, no previous studies have analysed the determinants of becoming an HGF from a USO. Second, hypotheses that, until now, had not been analysed in previous studies, in particular the fact of being a knowledge-intensive company, are tested. Third, the results obtained allow the establishment of recommendations to improve policies to support HGF-USO.